LINC00958 may be a new prognostic biomarker in various cancers: A meta-analysis and bioinformatics analysis - Zhang, Helin; Zhang, Guangming; Zhang, Fan; Yang, Xiaochun; Li, Erqiang; Wang, Bo; Xu, Peng; Zhang, Dengxiao; Guo, Lijun; Huang, Xiande (Frontiers in Genetics, 2022)
Background: There have been many studies on long non-coding RNAs (lncRNAs) as tumor markers. LINC00958 is a lncRNA that has been studied in a variety of tumor types. This meta-analysis aims to explore the relationship between LINC00958 and clinical prognosis and pathological characteristics in various cancers. Methods: We searched for related studies from PubMed, Web of Science, The Cochrane Library and Embase (up to October 2021). The association of LINC00958 expression with clinicopathological characteristics and prognosis was evaluated using the pooled odds ratios (ORs) or hazard ratios (HRs) with 95% confidence intervals (CIs). Results: 16 studies (1121 patients) were included in this meta-analysis, we found that overexpression of LINC00958 was associated with poor overall survival (OS) (HR = 1.84; 95% CI: 1.36-2.49; P < 0.001). We also found that LINC00958 overexpression was correlated with positive lymph node metastasis (LNM) (OR = 1.91; 95% CI: 1.39-2.63; P < 0.001), advanced degree of infiltration (OR = 1.64; 95% CI: 1.11-2.41; P = 0.013), advanced tumor-node-metastasis (TNM) stage (OR = 2.80; 95% CI: 1.48-5.33; P = 0.002). Other clinicopathological characteristics have no obvious correlation, such as age, sex, tumor size, distant metastasis, and differentiation grade (P > 0.05). Conclusion: In summary, the overexpression of LINC00958 is significantly correlated with poor OS, positive LNM, advanced degree of infiltration, and advanced TNM stage. LINC00958 might serve as a potential prognostic biomarker and therapeutic target for a variety of cancers. However, rigorous studies with large sample sizes are still needed for further research and demonstration.